2017
DOI: 10.1007/s11165-016-9596-9
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children’s Collaborative Science Learning Scaffolded by Tablets

Abstract: This paper reports on a project aiming to extend the current understanding of how emerging technologies, i.e. tablets, can be used in preschools to support collaborative learning of real-life science phenomena. The potential of tablets to support collaborative inquiry-based science learning and reflective thinking in preschool is investigated through the analysis of teacher-led activities on science, including children making timelapse photography and Slowmation movies. A qualitative analysis of verbal communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 24 publications
0
36
0
18
Order By: Relevance
“…The use of digital tablets in preschool education in Sweden is on the rise (e.g. Fridberg et al 2017;Marklund 2015;Marklund and Dunkels 2016;Nilsen 2014;Palmér 2015;Petersen 2015). Research results are beginning to provide insight into the influence of different tablet-related activities in preschool pedagogical practice, and on prospective benefits and limitations.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of digital tablets in preschool education in Sweden is on the rise (e.g. Fridberg et al 2017;Marklund 2015;Marklund and Dunkels 2016;Nilsen 2014;Palmér 2015;Petersen 2015). Research results are beginning to provide insight into the influence of different tablet-related activities in preschool pedagogical practice, and on prospective benefits and limitations.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
“…pictorial and textual) display modes that can contribute to both independent and collaborative learning and teaching activities (Petersen 2015). In addition, both Marklund and Dunkels (2016) and Bajovic (2018) have provided fruitful directions for how tablets can be combined with play to enhance children's digital literacy and the learning of specific subject knowledge, while Fridberg et al (2017) have shown how tablet activities can enhance children's reasoning about science concepts such as evaporation.…”
Section: Digital Tablets In Swedish Preschool Teachingmentioning
confidence: 99%
“…Maths concepts (such as classification, order, units, symmetries, graphics) are used explicitly in all the phases. Similarly for technology, where besides the use of tools to take data, to analyse it and to present results, technology can be utilised to express children's scientific explanation models, for example by means of 'stop-motion' technique (Fridberg et al, 2017).…”
Section: The Didactical Model Proposed In the Botstem Projectmentioning
confidence: 99%
“…También a finales del s. XX apareció la idea del "video-based laboratory" para analizar movimientos desde la cinemática (Beichner & Abbott, 1999), un formato que cuenta con una importante tradición en la enseñanza de la Física a través de softwares gratuitos tipo Tracker 8 (Alonso, 2011;Vera Mathias, Rivera Campos, Fuentes, & Romero Maltrana, 2015). En otros casos, las cámaras digitales son usadas para grabar y analizar de todo tipo de fenómenos naturales (Andrade-Lotero, 2014), así como para presentar estos fenómenos a través del slow motion (Koupil & Vícha, 2011) o el time lapse (Fridberg, Thulin, & Redfors, 2017). La recogida de datos experimentales para la indagación escolar, además, se ha abierto a nuevos fenómenos que puedan ocurrir fuera de las paredes de la escuela, mediante laboratorios remotos que reproducen fenómenos físicos sobre los que los estudiantes pueden tomar y analizar datos a tiempo real (Abdulwahed & Nagy, 2011;Lowe, Newcombe, & Stumpers, 2013).…”
Section: Herramientas Digitales Para La Matemática La Ciencia Y La Iunclassified